2017
DOI: 10.1002/pam.22023
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tulsa's Pre‐K Program on Middle School Student Performance

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 47 publications
5
56
2
Order By: Relevance
“…Head Start produced modest positive effects on immediate cognitive and social–emotional outcomes (Puma et al, ; Shager et al, ), but impacts on longer‐term outcomes have been mixed (Puma et al, , ). Similar results – with positive gains for children at the end of treatment but fade‐out in early elementary school – are consistent with earlier work (Barnett, ; Deming, ), though a follow‐up study of Tulsa's universal pre‐K program found sustained impacts on academic outcomes in middle school (Gormley, Phillips, & Anderson, ). Importantly, a recent study re‐analyzed data from the Head Start Impact Study and found significant variation in impacts based on child, center, and neighborhood characteristics (Morris et al, ).…”
Section: Introductionsupporting
confidence: 87%
“…Head Start produced modest positive effects on immediate cognitive and social–emotional outcomes (Puma et al, ; Shager et al, ), but impacts on longer‐term outcomes have been mixed (Puma et al, , ). Similar results – with positive gains for children at the end of treatment but fade‐out in early elementary school – are consistent with earlier work (Barnett, ; Deming, ), though a follow‐up study of Tulsa's universal pre‐K program found sustained impacts on academic outcomes in middle school (Gormley, Phillips, & Anderson, ). Importantly, a recent study re‐analyzed data from the Head Start Impact Study and found significant variation in impacts based on child, center, and neighborhood characteristics (Morris et al, ).…”
Section: Introductionsupporting
confidence: 87%
“…For example, one of our study’s key medium‐term outcomes—post‐prekindergarten enrollment in the BPS—has not been a focus in the literature to date, though it increasingly is a focus of localities that administer such programs. The only relevant evidence we are aware of is a recent study that found that Tulsa prekindergarten alumni were somewhat more likely to persist in the Tulsa Public Schools than were non‐Tulsa prekindergarten and non‐Tulsa Head Start attenders through eighth grade (Gormley, Phillips, & Anderson, ). There are, however, on‐the‐ground reports that schools in both New Orleans and DC—in which parent choice is a central feature of school assignment—have chosen to offer prekindergarten as a strategy to attract and retain families (D. Ewen, personal communication, June 19, 2017; Weixler, Lincove, & Gerry, ).…”
Section: When Might Prekindergarten Benefits Persist?mentioning
confidence: 99%
“…These estimates are presented in more detail elsewhere (Gormley, Phillips, and Anderson 2016) but are summarized here.…”
Section: Effects Of Tulsa Pre-k Program On Grade Retentionmentioning
confidence: 99%